Between a rock and a hard place : the power and powerlessness of transnational narratives among gay martinican men. - Murray, David A.B (American Antropological Association, 2000)
In Martinique, self-identified gay men often tell each other stories about gay communities in other societies. France and Martinique are central characters in these stories but their presence is largely negative: life in the former is criticized for its economic or racial hardships and life in the latter is criticized for homophobia, hypocrisy, and smallness, creating a frustrating catch-22 for these men. However, in these narratives Quebec often emerges as an ideal destination of racial and sexual freedom. In this paper, I argue that Quebec is signified as utopic in terms that are antithetical and therefore profoundly connected to impressions of social life in France and Martinique. At the same time, however, I maintain that these narratives also reveal common threads in the African-pan-American diasporic experience. Furthermore, these men's experiences of "gay" life in other countries demonstrate their awareness of a "global gay" identity, albeit one that is commercially and ideologically centered in Euro-American societies